Lei Sarbanes-Oxley: estudo sobre a divulgação de deficiências na avaliação dos controles internos - Lima, Raphael Moggioni de (2009)
Bankruptcy cases as the ones occured in U.S. economy after 2001 involving big corporations, as Enron, WorldCom and Global Crossing have exposed the fragilities of the companies internal control over financial reporting. Trying to reestablish the confidence in financial information provided to the investors and the market balance, the U.S. Congress enacted the Sarbanes Oxley Act (SOX), on 30 July 2002, introducing numerous changes to corporate governance and with respect to the controls over the results achieved. The rigorous changes introduced by SOX have been raised lots of discussions about the costs and benefits for the companies and the investors. This work aims to analyze the existing relations between the internal control over financial reporting disclosure (one requirement according to SOX) and the market performance of the companies shares. The analyses perform were based on regressions with brazilian companies informations issued in U.S. market share. The data used in the study are secondary, from the data base economática and the forms 20-F. The results show that the returns are badly affected in short term, however in longer periods there is no evidence between the internal control deficiencies disclosure and the increase in risk perceptions for the investors